Enhanced antibacterial properties and the cellular response of stainless steel through friction stir processing. Issue 2 (7th February 2019) - Perumal, Gopinath; Chakrabarti, Amrita; Grewal, Harpreet S.; Pati, Soumya; Singh, Shailja; Arora, Harpreet S.
Abstract: Biofilm related bacterial infection is one of the primary causes of implant failure. Limiting bacterial adhesion and colonization of pathogenic bacteria is a challenging task in health care. Here, a highly simplistic processing technique for imparting antibacterial properties on a biomedical grade stainless steel is demonstrated. Low-temperature high strain-rate deformation achieved using submerged friction stir processing resulted in a nearly single phase ultra-fine grain structure. The processed stainless steel demonstrated improved antibacterial properties for both Gram-positive and Gram-negative bacteria, significantly impeding biofilm formation during the in vitro study. Also, the processed stainless steel showed better compatibility with human fibroblasts manifested through apparent cell spreading and proliferation. The substantial antibacterial properties of the processed steel are explained in terms of the favorable electronic characteristics of the metal-oxide and by using classical Derjaguin–Landau–Verwey–Overbeek (DLVO) and the extended DLVO (XDLVO) approach at the cell–substrate interface.